2022
DOI: 10.1038/s43247-022-00496-5
|View full text |Cite
|
Sign up to set email alerts
|

Proximity to small-scale inland and coastal fisheries is associated with improved income and food security

Abstract: Poverty and food insecurity persist in sub-Saharan Africa. We conducted a secondary analysis of nationally representative data from three sub-Saharan Africa countries (Malawi, Tanzania, and Uganda) to investigate how both proximity to and engagement with small-scale fisheries are associated with household poverty and food insecurity. Results from the analysis suggest that households engaged in small-scale fisheries were 9 percentage points less likely to be poor than households engaged only in agriculture. Hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Conversely, loss of access to these fisheries could further erode an important nutritional safety net for these households. While subsistence fishing provides an indication of the contributions that small-scale fisheries livelihoods can provide to nutrition, such contributions are not limited to subsistence, as recent examples in Malawi, Uganda and Tanzania highlighted—where households located near small-scale fisheries were 13% more likely to achieve adequate food security and 15% less likely to be income poor than the most distant households 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, loss of access to these fisheries could further erode an important nutritional safety net for these households. While subsistence fishing provides an indication of the contributions that small-scale fisheries livelihoods can provide to nutrition, such contributions are not limited to subsistence, as recent examples in Malawi, Uganda and Tanzania highlighted—where households located near small-scale fisheries were 13% more likely to achieve adequate food security and 15% less likely to be income poor than the most distant households 21 .…”
Section: Discussionmentioning
confidence: 99%
“…In total, more than one-fifth of the country's surface area comprises surface waters (McCracken 1987). Small-scale fisheries in Lake Malawi and several other smaller inland lakes provide livelihoods throughout the value chain to > 200,000 Malawians and contribute USD $454 million annually, equivalent to 7.2% of Malawi's gross domestic product (Torell et al 2020, Simmance et al 2021. In addition to livelihood contributions, fish resources meaningfully contribute to food security and nutrition in Malawi.…”
Section: Study Areamentioning
confidence: 99%
“…Per capita consumption of aquatic foods ranges between countries from 0 to 100 kg per capita, annually (FAO, 2022), and is affected by multiple factors such as differences in cultural norms and perceptions, consumer preferences, and difficulties in distribution of perishable foods (UN Nutrition, 2021). Within countries, availability and consumption of aquatic foods may vary greatly, depending on proximity to water bodies and income status (Simmance et al, 2022a). For example, O'Meara et al (2021), found that children in Malawi and Zambia were more likely to consume fish if they lived close to inland fisheries and far from urban market centers (O'Meara et al, 2021).…”
Section: Availabilitymentioning
confidence: 99%